Synthesis, characterization and a reactivity study of some allyl palladium complexes bearing bidentate hemi-labile carbene or mixed carbene/PPh3 ligands. (24th November 2016) - Canovese, L.; Visentin, F.; Scattolin, T.; Santo, C.; Bertolasi, V.
Graphical abstract: Some novel palladium allyl and 2-Meallyl complexes bearing hemilabile spectator ligands containing a pivoting carbene and a labile wing with pyridine nitrogen or thioetheric sulfur as coordinating atom or PPh3 and again a carbene moiety have been synthesized and characterized . The solid state structures of two complexes and the mechanism of the reaction of amination of the allyl coordinated to two selected complexes have been also determined. The proposed mechanism suggests that the attack of the amine occurs trans to the carbene carbon irrespective of the hindrance by the substituent of the labile atom which however can heavily depress the reaction rate. Abstract: With the aim at synthesizing novel allyl complexes that can potentially act as catalysts in the Tsuji–Trost catalyzed reaction, we have synthesized and characterized some allyl and 2-Meallyl palladium derivatives with one hemilabile bidentate or two strong mono-coordinating spectator ligands. The hemilabile ligands are constituted by one nitrogen heterocyclic carbene (NHC) fragment acting as the pivot bearing a labile wing with a pyridine nitrogen or sulfur atom as the second stabilizing atom. One of two monodentate ligands is in all cases PPh3 whereas the other is a mono- or partially coordinated hemilabile carbene. The complexes were characterized by standard spectroscopic methods and elemental analysis and in two cases by SC-XRD technique. The reactivity of two selected complexes toward the Tsuji–Trost reaction was tested by stoichiometric allyl amination carried out with piperidine and the results of such a mechanistic investigation integrated by a computational study are also reported in this paper.